Answer:
Explanation:
1. You need to solve for x in all the equations and then compare the results with one another.
......................................................................................................................
I'll start with the equations on the left hand side
A.
3x + 6 = 4x + 7 ------------- Compare like terms
3x - 4x = 7 - 6
-x = 1
x = -1
B.
3(x + 6) = 4x + 7 --------------- Open the bracket
3x + 18 = 4x + 7 ------------ Collect like terms
3x - 4x = 7 - 18
-x = -11
x = 11
C.
4x + 3x = 7 - 6
7x = 1
x = 1/7
......................................................................................................................
Now to equations on the right hand side
1.
9x = 4x + 7------------- Collect like terms
9x - 4x = 7
5x = 7
x = 7/5
2.
3x + 18 = 4x + 7------------- Collect like terms
3x - 4x = 7 - 18
-x = -11
x = 11
3.
3x = 4x + 7---------------- Collect like terms
3x - 4x = 7
-x = 7
x = -7
4.
3x - 1 = 4x---------------- Collect like terms
3x - 4x = 1
-x = 1
x = -1
5.
7x = 1........................................................... Divide both sides by 7
7x/7 = 1/7
x = 1/7
.................................................................................................................................................................................
Now compare the results
1. Equation A " 3x + 6 = 4x + 7" equals to Equation 4 '"3x - 1 = 4x"
Because they both have the same results (x=-1)
2. Equation B "3(x + 6) = 4x + 7" equals to Equation 2 "3x + 18 = 4x + 7"
Because they both have the same results (x=11)
3. Equation C "4x + 3x = 7 - 6" equals to Equation 5 "7x = 1"
Because they both have the same results (x=1/7)
2. Equation A: -3(x + 7) = 24
Equation B: x + 7 = -8
Statement D is correct.
Divide both sides of equation A by -3 gives x+7=-8 which is equation B
To check
Let's divide both sides of equation A by -3
-3(x+7)/(-3) = 24/(-3)
x + 7 = -8